The Role of Artificial Intelligence in Education: A Systematic Literature Review - Imam Karya Bakti; Zulkarnain; Ayuningtias Yarun; Rusdi; Mokhamad Syaifudin; Hammis Syafaq (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
The rapid advancement of computing technology has facilitated the implementation of AIED (Artificial Intelligence in Education) applications. AIED refers to the use of AI (Artificial Intelligence) technologies or application programmes in educational settings to facilitate teaching, learning or decision-making. This research aims to identify the role of AI in education. This research utilises a Systematic Literature Review (SLR) using PRISMA analysis to identify AI’s role in education. An important finding of this research is that with the help of AI technology, which simulates human intelligence to make inferences, judgements, or predictions, computer systems can provide personalised guidance, support, or feedback to students as well as assist teachers or policymakers in making decisions. These findings indicate the important role AI can play in education to improve the efficiency and effectiveness of learning. However, it is important to note that AI is not a substitute for teachers. The role of teachers as facilitators and supporters of learning remains important in the context of AI use. Keywords: Artificial Intelligence (AI), Education, Systematic Literature Review (SLR).